How Can Hotel Employees Produce Workplace Environmentally Friendly Behavior? The Role of Leader, Corporate and Coworkers - Zheng, Shanting; Jiang, Lin; Cai, Wenjing; Xu, Binfeng; Gao, Xiaopei (Frontiers in Psychology, 2021)
Although previous studies have acknowledged that leaders’ such environmental behaviors and environmental issues are becoming critical for the long-term development, little research has focused on why, how and when does environmentally-specific servant leadership contribute to employees’ workplace environmentally friendly behavior in hotel industry. This paper aims to fill in this research gap through integrating social identity theory and social learning theory to test employees’ green role identity as a mediator and their perceived corporate environmental responsibility and coworkers’ work group green advocacy as moderators in the relationship between environmentally-specific servant leadership and workplace environmentally friendly behavior. Using a sample of 527 leader–follower dyads from six hotels in mainland China at two points of time, we found that employees’ green role identity mediates the positive relationship between environmentally-specific servant leadership and employees’ workplace environmentally friendly behavior. Moreover, employees’ perceived corporate environmental responsibility and coworkers’ work group green advocacy were found to moderate the relationship between environmentally-specific servant leadership and green role identity and between green role identity and workplace environmentally friendly behavior respectively. Theoretical and practical implications are discussed.